Transformation of User Manual of Numerical Analysis Library into the HTML-format - Volchenskova, N.I.; Zyuryaeva, I.V.; Lamzina, T.V. (Numerical Methods and Programming (Vychislitel'nye Metody i Programmirovanie), 2000)
Some software tools for automated transformation of User Manual of Numerical Analysis Library into HTML-documents are considered. Methods for representation of structural sections of the Manual and the corresponding templates are given. A number of recommendations for using the transformation tools are discussed.